Catalytic performance of Cu/ZnO/Al2O3/ZrO2 for slurry methanol synthesis from CO hydrogenation: Effect of Cu/Zn molar ratio - Shaharun, S. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Catalytic hydrogenation of carbon dioxide (CO2) to methanol is an attractive way to recycle and utilize CO2. A series of Cu/ZnO/Al2O3/ZrO2 catalysts (CZAZ) containing different molar ratios of Cu/Zn were prepared by the co-precipitation method. The catalysts were characterized by temperature-programmed reduction (TPR), field emission scanning electron microscopy-energy dispersive x-ray analysis (FESEM-EDX) and X-ray diffraction (XRD). Higher surface area, SABET values (42.6-59.9 m2/g) were recorded at low (1) and high (5) Cu/Zn ratios with the minimum value of 35.71 m2/g was found for a Cu/Zn of 3. The reducibility of the metal oxides formed after calcination of catalyst samples was also affected due to change in metal-support interaction. At a reaction temperature of 443 K, total gas pressure of 3.0 MPa and 0.1 g/ mL of the CZAZ catalyst, the selectivity to methanol decreased as the Cu/Zn molar ratio increased, and the maximum selectivity of 93.9 was achieved at Cu/Zn molar ratio of 0.33. With a reaction time of 3h, the best performing catalyst was CZAZ75 with Cu/Zn molar ratio of 5 giving methanol yield of 6.4.